KONFIGURASI KATA SAM’, BASHAR, DAN FU’AD DALAM AL-QUR’AN MENURUT TINJAUAN ILM AL-MA’ANIY - Siddiq, Mahfudz (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
In language and literature perspective, the Qur′anic style has uniqueness because it has specific characteristic, model, and configuration in its style, word, and structure. Al-Qur′an as a miracle of the God revealed to Muhammad peace be upon him is a miracle text of language and literature, although it can not be categorized as literary text, but it uses literary approach in delivering God ideas about world life and hereafter. In this article, the writer tries to discover Qur′anic uniqueness to observe tree words that are always mentioned in a series; sam’ (hear), bashar (see), and fu′aad (heart). In this case, the writer uses al-ma’aaniy, one of al-balaghah branches to analyze Qur′anic verses. The aim is to explain uniqueness of its specific characteristic, model, and configuration used in Qur′anic style in order to explain those tree words. The findings are that the expression of those three words expressed in a series, are revealed in six verses. (1) Surah al-Nahl (16) ayat 78; (2) Surah al-Isra′ (17) ayat 36; (3) Surah al-Mu’minun (23) ayat 78; (4) Surah al-Sajdah (32) ayat 9; (5) Surah al-Ahiqaf (46) ayat 26; dan (6) Surah al-Mulk (67) ayat 23. The sense expressions have reached the perfectness, fashahah or the harmony and compactness among one phrase and the next phrase. In other word the fashahah and balaghah of the Al Quran is incomparable.